Evaluation of the Hematologic Safety of Same Day Versus Standard Administration (24- to 72-Hour Delay) of Pegfilgrastim in Gynecology Oncology Patients Undergoing Cytotoxic Chemotherapy. Issue 7 (1st September 2015) - Billingsley, Caroline C.; Jacobson, Samuel N.; Crafton, Sarah M.; Crim, Aleia K.; Li, Quan; Hade, Erinn M.; Cohn, David E.; Fowler, Jeffrey M.; Copeland, Larry J.; Salani, Ritu; Backes, Floor J.; O'Malley, David M.
Abstract : Objective: We assessed the safety and efficacy of administration of pegfilgrastim on the same day compared with standard administration 24 to 72 hours after chemotherapy in patients with gynecologic malignancies. Methods: A retrospective review was conducted on patients undergoing pegfilgrastim to mitigate the myelosuppressive consequences of chemotherapy. The primary outcome was incidence of grade 3 to 4 neutropenia following pegfilgrastim for same-day administration (D1) versus standard administration (D2+). Secondary outcomes included dose delay, regimen change, hospitalization due to neutropenia, and incidence of febrile neutropenia. Results: Four hundred twenty-one patients with 2071 administrations of pegfilgrastim were included. Five hundred six administrations of pegfilgrastim were given on D1 compared with 1565 administrations on D2+. The most common malignancy was ovarian cancer (79.1%), followed by endometrial (14.5%). Comparing the D1 and D2+ cohorts, noninferiority was not established for the incidence of grade 3 to 4 neutropenia (2.6% vs 1.8%, adjusted relative risk [aRR], 1.6; 90% confidence interval [CI], 0.87–3.2) or dose modification (6.5% vs 4.9%; aRR, 1.3; 90% CI, 0.9–1.8). However, the rate of treatment delays (7.3% vs 9.4%; aRR, 0.8; 90% CI, 0.6–1.1) in the D1 and D2+ groups suggested that delays in the D1 group were not more common than in the D2+ group. Conclusions: The incidence of hematologic toxicities and dose modification in patients receiving same-day pegfilgrastim were not as low as in those undergoing standard administration. However, treatment delays were found to be no more frequent in those receiving same-day pegfilgrastim versus standard administration. Same-day administration of pegfilgrastim is a reasonable option.